Super-Low Dose Lipopolysaccharide Dysregulates Neutrophil Migratory Decision-Making - Boribong, Brittany P.; Lenzi, Mark J.; Li, Liwu; Jones, Caroline N. (Frontiers in Immunology, 2019)
Neutrophils are the first responders to infection and play a pivotal role in many inflammatory diseases, including sepsis. Recent studies have shown that lipopolysaccharide (LPS), a classical pattern recognition molecule, dynamically programs innate immune responses. In this study, we show that pre-treatment with super low levels of LPS [1 ng/mL] significantly dysregulate neutrophil migratory phenotypes, including spontaneous migration and altering neutrophil decision-making. To quantify neutrophil migratory decision-making with single-cell resolution, we developed a novel microfluidic competitive chemotaxis-chip (μC3) that exposes cells in a central channel to competing chemoattractant gradients. In this reductionist approach, we use two chemoattractants: a pro-resolution (N-Formyl-Met-Leu-Phe (fMLP)) and pro-inflammatory (Leukotriene B4, LTB4) chemoattractant to model how a neutrophil makes a decision to move toward a bacterial infection versus an inflammatory signal. We demonstrate that naïve neutrophils migrate towards the primary pro-resolution signal in higher percentages than toward the secondary pro-inflammation signal. As expected, we found that training with high dose LPS [100 ng/mL] influences a higher percentage of neutrophils to migrate towards the pro-resolution signal, while reducing the percentage of neutrophils that migrate towards the pro-inflammatory signal. Surprisingly, super low-dose LPS [1 ng/mL] significantly changes the ratios of migrating cells and an increased percentage of cells migrate toward the pro-inflammatory signal. Significantly, there was also an increase in the numbers of spontaneously migrating neutrophils after treatment with super low-dose LPS. These results shed light onto the directional migratory decision-making of neutrophils exposed to inflammatory training signals. Understanding these mechanisms may lead to the development of pro-resolution therapies that correct the neutrophil compass and reduce off-target organ damage.